Laminated solar cell with dual-mode port and preparation method and application thereof

By using a double-sided conductive grid film as the intermediate connecting layer in the stacked solar cells, the current mismatch and long preparation period in the two-end battery structure are solved, and the weight and cost of the four-end battery are reduced, thereby improving the overall photoelectric conversion efficiency.

CN119546048APending Publication Date: 2025-02-28PEKING UNIV YANGTZE RIVER DELTA INST OF OPTOELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646656.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing stacked solar cells have problems of current mismatch and long production cycles in the two-end battery structures, while the four-end battery structure has problems of complex manufacturing processes and high cost.

Method used

A double-sided conductive grid film is used as the intermediate connecting layer, providing optional port usage, suitable for both and four-end stacked batteries. The film consists of a metal grid and a flexible transparent layer to connect the top and bottom cells, enabling independent preparation and lightweight design.

Benefits of technology

In the stacked batteries at both ends, the battery efficiency is improved and the preparation cycle is shortened; in the stacked batteries at four ends, the weight and cost are reduced, and the light transmittance and photoelectric conversion efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546048A_ABST
    Figure CN119546048A_ABST
Patent Text Reader

Abstract

The invention provides a laminated solar cell with a dual-mode port and a preparation method and application thereof, and belongs to the technical field of solar cells. The laminated solar cell is a two-end laminated solar cell or a four-end laminated solar cell; the laminated solar cell comprises a top cell, a bottom cell and a double-sided conductive grid film located between the top cell and the bottom cell. The double-sided conductive grid film comprises a metal grid and a flexible transparent layer filled into meshes of the metal grid. According to the invention, the double-sided conductive grid film is used as a middle connecting layer, and a selectable port use mode is provided. In the two-end laminated cell, the top cell and the bottom cell can be independently prepared, the cell efficiency is improved, and the preparation period of the two-end laminated cell is saved; in the four-end laminated cell, the top cell has the advantages of light weight, small volume and low cost, and the bottom cell does not need to additionally prepare a metal electrode grid line, so that the problem of large weight of the four-end laminated cell is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a stacked solar cell with a dual-mode port, a preparation method and an application thereof. Background Art

[0002] The resource depletion and environmental pollution problems caused by the growth of global energy demand have prompted countries to accelerate the development of renewable energy. Solar energy has become a key choice because of its cleanliness and sustainability. In recent years, the commercial application of single-junction solar cells (such as crystalline silicon cells) has made significant progress, but its photoelectric conversion efficiency is close to the theoretical limit. In order to further improve the conversion efficiency of solar cells, tandem cell technology has emerged. As the top cell of tandem cells, perovskite solar cells have gradually become ideal candidate materials due to their adjustable band gap, excellent photoelectric properties, low-cost preparation process, and potential for application in flexible and transparent cells. In addition, its spectral complementarity with the bottom cell is strong, which can maximize the utilization of the solar spectrum of the entire tandem cell, thereby improving the overall photoelectric conversion efficiency of the device.

[0003] At present, the design of stacked solar cells mainly includes a two-terminal cell structure and a four-terminal cell structure. Among them, the preparation process of the two-terminal cell structure is relatively simple. The top cell and the bottom cell are connected in series by sharing an intermediate composite layer, but there is a current mismatch problem, which limits the overall cell efficiency. Solving the above problems requires precise optimization of the upper and lower layer materials, which is a process with high difficulty. At the same time, the top cell and the bottom cell cannot be prepared at the same time in the prior art, which greatly increases the preparation cycle of the device. In contrast, the four-terminal cell gives the cell greater design freedom and modular design potential due to the independence of its top cell and bottom cell. However, the four-terminal cell involves a complex combination of multiple electrodes and battery layers, making its manufacturing process more cumbersome and more costly. In addition, after the independently prepared top cell is superimposed on the bottom cell, the overall volume and weight of the battery increase, which to a certain extent limits the widespread promotion of the four-terminal battery in portable devices or other weight-sensitive applications.

[0004] Therefore, how to solve the current mismatch and long device preparation cycle problems in the two-terminal battery structure, as well as the complex and high cost manufacturing process in the four-terminal battery structure, are topics that urgently need to be studied. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a stacked solar cell with dual-mode ports, as well as a preparation method and application. The present invention uses a double-sided conductive grid film as an intermediate connecting layer, and provides an optional port usage method, which is not only applicable to two-terminal stacked batteries, but also to four-terminal stacked batteries. In the two-terminal stacked battery, the top battery is flexible, thin and has good coverage, and it and the bottom battery can be prepared independently, which improves the battery efficiency and greatly saves the preparation cycle of the two-terminal stacked battery; in the four-terminal stacked battery, the top battery has the advantages of light weight, small size and low cost, and the bottom battery does not require additional preparation of metal electrode grid lines, which effectively solves the problem of large weight of the four-terminal stacked battery and is suitable for a variety of photovoltaic application scenarios. The stacked solar cell has excellent photoelectric conversion efficiency and bright development prospects.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a tandem solar cell with dual-mode ports, wherein the tandem solar cell is a two-terminal tandem solar cell or a four-terminal tandem solar cell.

[0008] The stacked solar cell comprises a top cell, a bottom cell and a double-sided conductive mesh film located between the top cell and the bottom cell.

[0009] The double-sided conductive mesh film comprises a metal mesh and a flexible transparent layer filled in the meshes of the metal mesh.

[0010] Conventional stacked solar cells can only use one port, where the connection of the two-terminal stacked cells in series requires the current and battery structure of the top cell and the bottom cell to be matched, and the bottom cell and the top cell need to be prepared in sequence. The four-terminal battery connection allows the top and bottom cells to be prepared independently, and the selection and preparation of the top and bottom cells can be more flexible, and the energy range of the entire solar spectrum can be more easily covered without considering current matching. However, this also brings a more cumbersome preparation process and the overall weight of the device.

[0011] To this end, the present invention uses a double-sided conductive mesh film as an intermediate connection layer, and provides an optional port usage method, which is not only applicable to two-terminal laminated batteries, but also to four-terminal laminated batteries. In the two-terminal laminated battery, the top battery is flexible, thin and has good coverage, and it and the bottom battery can be prepared independently, which improves the battery efficiency and greatly saves the preparation cycle of the two-terminal laminated battery; in the four-terminal laminated battery, the top battery has the advantages of light weight, small size and low cost, and the bottom battery does not need to prepare additional metal electrode grid lines, which effectively solves the problem of large weight of the four-terminal laminated battery and is suitable for a variety of photovoltaic application scenarios. The laminated solar cell has excellent photoelectric conversion efficiency and bright development prospects.

[0012] In the present invention, in a two-terminal stacked battery, the top cell and the bottom cell can be independently prepared and assembled and disassembled. In a four-terminal stacked battery, the structure of the top cell does not need to match the structure of the bottom cell, and the top cell can adopt a formal structure (nip structure) or an inverted structure (pin structure).

[0013] Preferably, the thickness of the double-sided conductive mesh film is 1-5 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0014] In the present invention, a double-sided conductive mesh film with a suitable thickness is helpful to increase the mechanical strength of the film.

[0015] Preferably, the line width of the metal grid is 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0016] In the present invention, a metal grid with a suitable line width helps to improve the current transmission capability.

[0017] Preferably, the line spacing of the metal grid is 0.2-0.8 mm, for example, it can be 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm or 0.8 mm.

[0018] In the present invention, a metal grid with a suitable line spacing helps to balance electrical conductivity and light transmittance.

[0019] Preferably, the metal grid is a rectangular grid, for example, a square grid, etc.

[0020] Preferably, the material of the metal grid includes any one of nickel, copper or zinc, or a combination of at least two of them.

[0021] Preferably, the flexible transparent layer includes any one of a polyethylene terephthalate layer, a polycarbonate layer or a parylene layer, or a combination of at least two thereof.

[0022] It should be noted that parylene is a protective polymer material and is the common name for a unique series of polyparaxylene polymers.

[0023] Preferably, in the double-sided conductive mesh film, the duty cycle of the metal mesh is 5-8%, for example, 5%, 6%, 7% or 8%.

[0024] In the present invention, the metal mesh with an appropriate mass content in the double-sided conductive mesh film helps to achieve both efficient current transmission and high light transmittance.

[0025] Preferably, the thickness of the metal grid is equal to the thickness of the flexible transparent layer.

[0026] Preferably, the flexible transparent layer is a single-layer flexible transparent layer or a composite flexible transparent layer.

[0027] Preferably, the composite flexible transparent layer comprises a bottom flexible transparent layer, an adhesive layer and a top flexible transparent layer which are stacked.

[0028] In the present invention, an adhesive layer is disposed between the bottom flexible transparent layer and the top flexible transparent layer, which helps to enhance the bonding force between the metal grid and the flexible transparent layer.

[0029] Preferably, the thickness ratio of the bottom flexible transparent layer to the top flexible transparent layer is 1:(0.5-2), illustratively, for example, 1:0.5, 1:1, 1:1.5 or 1:2.

[0030] Preferably, the thickness of the adhesive layer is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0031] In the present invention, an adhesive layer with a suitable thickness is helpful to enhance the bonding force between the metal grid and the flexible transparent layer. If the thickness is too large, it is not conducive to obtaining a high light transmittance.

[0032] Preferably, the material of the bonding layer includes any one of polydimethylsiloxane, polymethyl methacrylate or polyurethane, or a combination of at least two of them.

[0033] Preferably, the top cell comprises a perovskite solar cell.

[0034] Preferably, the perovskite solar cell includes a transparent electrode layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and an electrode which are stacked in a direction away from the double-sided conductive grid film.

[0035] Preferably, the transparent electrode layer includes any one of an ITO (indium tin oxide) layer, an IZO (indium zinc oxide) layer, an FTO (fluorine-doped tin oxide) layer or an AZO (aluminum-doped zinc oxide) layer, or a combination of at least two of them.

[0036] Preferably, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties.

[0037] Preferably, the first charge transport layer is an electron transport layer, and the second charge transport layer is a hole transport layer, or the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer.

[0038] Preferably, the electron transport layer comprises a titanium dioxide layer, a tin oxide layer, a zinc oxide layer, a C 60 Any one of the layers or PCBM layers or a combination of at least two.

[0039] Preferably, the hole transport layer comprises a Spiro-OMeTAD layer, a PEDOT layer, a NiO x Any one of a CuSCN layer, a PTAA layer or a P3HT layer, or a combination of at least two thereof.

[0040] Preferably, the electrode is a metal electrode, for example, an Ag electrode.

[0041] Preferably, a transparent conductive layer is further provided between the second charge transport layer and the electrode, and the material of the transparent conductive layer includes ITO.

[0042] Preferably, the bottom cell comprises any one of a silicon-based cell, a copper indium gallium selenide cell, a cadmium telluride cell or a perovskite solar cell, or a combination of at least two thereof. Exemplarily, the silicon-based cell may be, for example, a monocrystalline silicon solar cell.

[0043] In a second aspect, the present invention provides a method for preparing a stacked solar cell with a dual-mode port as described in the first aspect, the preparation method comprising the following steps:

[0044] A top cell is prepared on one side surface of the double-sided conductive mesh film and then stacked on the bottom cell so that the other side surface of the double-sided conductive mesh film fits the bottom cell to obtain the stacked solar cell with dual-mode ports.

[0045] The preparation process provided by the invention is simple and has low manufacturing cost, and has good development prospects.

[0046] Preferably, the method for preparing the double-sided conductive mesh film comprises the following steps:

[0047] A flexible transparent film is deposited on a rigid substrate, and then patterned to form a blank grid, wherein the rigid substrate is exposed by the blank grid.

[0048] The blank grids are filled with metal material to form metal grids, and then the rigid substrate is peeled off to obtain the double-sided conductive grid film.

[0049] Preferably, the rigid substrate comprises any one of a conductive silicon wafer, ITO glass or FTO glass.

[0050] Preferably, the deposition method of the flexible transparent film includes any one of a solution processing method, a physical vapor deposition method or a chemical vapor deposition method.

[0051] Preferably, the patterning process includes any one of laser etching, photolithography, screen printing or thermal evaporation.

[0052] The filling method of the metal material includes an electroplating method. In the electroplating method, the current size is 30-50mA, such as 30mA, 35mA, 40mA, 45mA or 50mA, and the electroplating time is 10-20min, such as 10min, 15min or 20min.

[0053] Preferably, the flexible transparent film is a single-layer flexible transparent film or a composite flexible transparent film.

[0054] The preparation method of the composite flexible transparent film comprises:

[0055] A bottom flexible transparent film, a bonding layer and a top flexible transparent film are sequentially deposited on one side surface of the rigid substrate.

[0056] The bonding layer may be prepared by a solution method, such as a spin coating method.

[0057] The present invention does not limit the preparation method of the perovskite solar cell. Exemplarily, the preparation method of the perovskite solar cell adopts the following steps:

[0058] A transparent electrode layer, an electron transport layer, a perovskite absorption layer, a hole transport layer and a metal electrode are sequentially deposited on the double-sided conductive grid film.

[0059] Among them, the deposition method of the transparent electrode layer includes magnetron sputtering; the deposition method of the electron transport layer includes spin coating; the chemical formula of the perovskite absorption layer is ABX3 (A is any one of formamidinium ion, methylamine ion or cesium ion or a combination of at least two, B is lead ion and / or tin ion, X is halogen ion), and the deposition method includes spin coating; the deposition method of the hole transport layer includes spin coating; the deposition method of the metal electrode includes thermal evaporation.

[0060] In a third aspect, the present invention provides an application of the stacked solar cell with dual-mode ports as described in the first aspect in the photovoltaic field.

[0061] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] (1) The present invention uses a double-sided conductive mesh film as an intermediate connection layer and provides an optional port usage method, which is not only applicable to two-terminal stacked batteries, but also to four-terminal stacked batteries. In the two-terminal stacked batteries, the top battery is flexible, thin and has good coverage, and it breaks through the time and space limitations of the traditional two-terminal stacked batteries in the preparation process, not only allowing the top battery and the bottom battery to be prepared independently, but also improving the battery efficiency, greatly saving the preparation cycle of the two-terminal stacked batteries; in the four-terminal stacked batteries, the top battery has the advantages of light weight, small size and low cost, and the double-sided conductive mesh film can replace the metal grid line battery on the top of the bottom battery, so that the bottom battery does not need to prepare additional metal electrode grid lines, effectively solving the problem of heavy weight of the four-terminal stacked batteries, while improving the light transmittance of the stacked batteries, suitable for a variety of photovoltaic application scenarios. The stacked solar cell has excellent photoelectric conversion efficiency.

[0064] (2) The preparation process provided by the present invention is simple and has low manufacturing cost, and has good development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a schematic diagram of the structure of the stacked solar cell provided in Example 1 of the present invention.

[0066] Figure 2 This is a schematic diagram of the structure of a stacked solar cell provided in Example 2 of the present invention.

[0067] Among them, 1-top battery; 11-transparent electrode layer; 12-electron transport layer; 13-perovskite absorption layer; 14-hole transport layer; 15-transparent conductive layer; 16-Ag grid electrode; 2-bottom battery, 3-double-sided conductive grid film. DETAILED DESCRIPTION

[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0069] Example 1

[0070] This embodiment provides a tandem solar cell with dual-mode ports, wherein the tandem solar cell is a two-terminal tandem solar cell.

[0071] The structural schematic diagram of the stacked solar cell is as follows Figure 1 As shown, it includes a top battery 1, a bottom battery 2 and a double-sided conductive mesh film 3 located between the top battery 1 and the bottom battery 2.

[0072] The top cell 1 is a perovskite solar cell with a nip structure, and includes a stacked transparent electrode layer 11, an electron transport layer 12, a perovskite absorption layer 13, a hole transport layer 14, a transparent conductive layer 15 and an Ag grid line electrode 16 along the direction away from the double-sided conductive grid film 3; the transparent electrode layer 11 is a FTO layer with a thickness of 100nm; the electron transport layer 12 is a tin oxide layer, the chemical formula of the perovskite absorption layer 13 is MAPbI3, and the hole transport layer 14 is a Spiro-MeOTAD layer; the transparent conductive layer 15 is an ITO layer with a thickness of 100nm.

[0073] The double-sided conductive mesh film 3 includes a metal mesh and a single-layer flexible transparent layer filled in the mesh of the metal mesh; the thickness of the double-sided conductive mesh film 3 is 3μm; the line width of the metal mesh is 40μm; the line spacing of the metal mesh is 0.5mm; the metal mesh is a square mesh; the material of the metal mesh is nickel; the single-layer flexible transparent layer is a parylene layer; in the double-sided conductive mesh film 3, the mass content of the metal mesh is 6%; the thickness of the metal mesh is equal to the thickness of the single-layer flexible transparent layer.

[0074] The bottom cell 2 is a monocrystalline silicon solar cell, and includes a back electrode layer, a passivation layer, a monocrystalline silicon light absorption layer and an ITO layer stacked in a direction close to the double-sided conductive mesh film 3 .

[0075] This embodiment also provides a method for preparing the above-mentioned laminated solar cell, and the preparation method comprises the following steps:

[0076] (1) Preparation of double-sided conductive mesh film:

[0077] Using a conductive silicon wafer as a substrate, the conductive silicon wafer was immersed in deionized water, acetone, deionized water and isopropanol in turn for ultrasonic cleaning for 10 minutes, and then a flexible transparent parylene film with a thickness of 3 μm was deposited on one surface of the conductive silicon wafer by chemical vapor deposition.

[0078] The flexible transparent parylene film was patterned by laser etching to obtain a blank square grid pattern with a line width of 40 μm and a line spacing of 0.5 mm. The current parameter of the laser etching was set to 5 mA. Then, the electroplating method was used to electroplate for 15 minutes at a current of 40 mA to fill nickel metal at the blank grid lines to form a metal network with a thickness of 3 μm. Then, the conductive silicon wafer was peeled off to obtain a double-sided conductive grid film.

[0079] (2) Preparation of top battery:

[0080] The double-sided conductive mesh film was transferred onto a cleaned glass sheet, and a FTO layer with a thickness of 100 nm was deposited as a transparent electrode layer by magnetron sputtering.

[0081] SnO2 dispersion and deionized water were prepared into SnO2 solution in a mass ratio of 1:4. The prepared SnO2 solution was shaken for 1 hour to be fully mixed, and then filtered using a 0.45μm filter head. The filtered SnO2 solution was spin-coated on the FTO layer at a speed of 3000rpm for 30s. After the spin coating, it was annealed on an annealing table at 150℃ for 30min to obtain a tin oxide layer.

[0082] PbI2 and MAI were dissolved in a mixed solvent (DMF:DMSO=9:1 (volume ratio)) at a molar ratio of 1:1, and stirred at 70°C for 2 hours to obtain a perovskite precursor solution with a concentration of 1.2 mol / L; in a glove box, the perovskite precursor solution was spin-coated on the tin oxide layer at 3000 rpm for 30 seconds, and 100 μL of anti-solvent chlorobenzene was added 10 seconds after the spin coating was completed. After the spin coating was completed, the solution was annealed at 150°C for 20 minutes to obtain a perovskite light-absorbing layer with a chemical formula of MAPbI3.

[0083] The Spiro-MeOTAD solution was dropped onto the perovskite light-absorbing layer and spin-coated at 4000 rpm for 45 s to obtain the Spiro-MeOTAD layer.

[0084] An ITO layer with a thickness of 100 nm was deposited on the Spiro-MeOTAD layer as a transparent conductive layer by magnetron sputtering, and then an Ag gate line electrode was deposited on the ITO layer by thermal evaporation.

[0085] The glass sheet is peeled off to obtain a top cell deposited on the double-sided conductive mesh film.

[0086] (3) Using a monocrystalline silicon solar cell as a bottom cell, stacking the top cell deposited on the double-sided conductive mesh film on the top ITO layer of the bottom cell, so that the double-sided conductive mesh film adheres to the ITO layer, thereby obtaining the stacked solar cell with a dual-mode port.

[0087] Example 2

[0088] This embodiment provides a tandem solar cell with dual-mode ports, wherein the tandem solar cell is a four-terminal tandem solar cell.

[0089] The structural schematic diagram of the stacked solar cell is as follows Figure 2 As shown, it includes a top battery 1, a bottom battery 2 and a double-sided conductive mesh film 3 located between the top battery 1 and the bottom battery 2.

[0090] The top cell 1 is a perovskite solar cell with a pin structure, and includes a transparent electrode layer 11, a hole transport layer 14, a perovskite absorption layer 13, an electron transport layer 12, a transparent conductive layer 15 and an Ag grid electrode 16 stacked in a direction away from the double-sided conductive grid film 3; the transparent electrode layer 11 is an ITO layer with a thickness of 150nm; the hole transport layer 14 is NiO x layer, with a thickness of 30 nm; the chemical formula of the perovskite absorption layer 13 is Cs 0.17 FA 0.83 Pb(I 0.75 Br 0.25 ) 3, the electron transport layer 12 comprises C with a thickness of 20nm 60 layer and a PCBM layer with a thickness of 40nm; the transparent conductive layer 15 is an ITO layer with a thickness of 100nm.

[0091] The double-sided conductive mesh film 3 includes a metal mesh and a composite flexible transparent layer filled in the mesh of the metal mesh; the thickness of the double-sided conductive mesh film 3 is 3μm; the line width of the metal mesh is 40μm; the line spacing of the metal mesh is 0.5mm; the metal mesh is a square mesh; the material of the metal mesh is nickel; the composite flexible transparent layer includes a bottom parylene layer, an adhesive layer and a top parylene layer stacked in a direction close to the top battery, the thickness ratio of the bottom parylene layer to the top parylene layer is 1:1, the thickness of the adhesive layer is 1μm, and the material is polydimethylsiloxane; in the double-sided conductive mesh film, the mass content of the metal mesh is 6%; the thickness of the metal mesh is equal to the thickness of the composite flexible transparent layer.

[0092] The bottom cell 2 is a monocrystalline silicon solar cell, and includes a stacked back electrode layer, a passivation layer, a monocrystalline silicon light absorption layer and an ITO layer along the direction close to the double-sided conductive mesh film 3. The double-sided conductive mesh film 3 serves as the front electrode layer of the monocrystalline silicon solar cell.

[0093] This embodiment also provides a method for preparing the above-mentioned laminated solar cell, and the preparation method comprises the following steps:

[0094] (1) Preparation of double-sided conductive mesh film:

[0095] A conductive silicon wafer was used as a substrate and was sequentially immersed in deionized water, acetone, deionized water and isopropanol for ultrasonic cleaning for 10 minutes. Then, a bottom flexible transparent parylene film with a thickness of 1 μm was deposited on one surface of the conductive silicon wafer by chemical vapor deposition. Subsequently, a layer of polydimethylsiloxane film with a thickness of 1 μm was spin-coated on the bottom flexible transparent parylene film at a rotation speed of 2000 rpm. Then, a layer of top flexible transparent parylene film with a thickness of 1 μm was deposited by chemical vapor deposition to form a composite flexible transparent film.

[0096] The composite flexible transparent film is patterned by laser etching to obtain a blank square grid pattern with a line width of 40 μm and a line spacing of 0.5 mm. The current parameter of the laser etching is set to 5 mA. Then, the electroplating method is used to electroplate for 15 minutes at a current of 40 mA to fill nickel metal at the blank grid lines to form a metal network with a thickness of 3 μm. Then, the conductive silicon wafer is peeled off to obtain a double-sided conductive grid film.

[0097] (2) Preparation of top battery:

[0098] The double-sided conductive mesh film was transferred onto a cleaned glass sheet, and an ITO layer with a thickness of 150 nm was deposited as a transparent electrode layer by magnetron sputtering.

[0099] NiO x The precursor solution was spin-coated on the ITO layer at a speed of 3000 rpm for 30 seconds, and then placed on an annealing table at 100°C for 10 minutes to obtain a NiO layer with a thickness of 30 nm. x layer.

[0100] PbI2, PbBr2, FAI, FABr and CsI were dissolved in a mixed solvent (DMF:DMSO=4:1 (volume ratio)) at a molar ratio of 0.75:0.25:0.83:0.83:0.17, and stirred at 70°C for 1 hour to obtain a perovskite precursor solution; in a glove box, the perovskite precursor solution was dropped onto NiO xThe layer was spin-coated at 1000 rpm for 10 seconds, and then at 4000 rpm for 30 seconds. 10 seconds after the spin coating, 100 μL of anti-solvent chlorobenzene was added. After the spin coating, the layer was annealed at 100 ° C for 20 minutes to obtain a Cs 0.17 FA 0.83 Pb(I 0.75 Br 0.25 )3's perovskite light-absorbing layer.

[0101] By thermal evaporation, a 20 nm thick C 60 layer and a PCBM layer with a thickness of 40 nm.

[0102] An ITO layer with a thickness of 100 nm was deposited on the PCBM layer as a transparent conductive layer by magnetron sputtering, and then an Ag gate line electrode was deposited on the ITO layer by thermal evaporation.

[0103] The glass sheet is peeled off to obtain a top cell deposited on the double-sided conductive mesh film.

[0104] (3) Using a monocrystalline silicon solar cell as a bottom cell, stacking the top cell deposited on the double-sided conductive mesh film on the top ITO layer of the bottom cell, so that the double-sided conductive mesh film adheres to the ITO layer, thereby obtaining the stacked solar cell with a dual-mode port.

[0105] Example 3

[0106] The difference between this embodiment and embodiment 1 is that the thickness of the flexible transparent parylene film is 0.5 μm by adjusting the deposition parameters of the chemical vapor deposition method in step (1).

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Example 4

[0109] The difference between this embodiment and embodiment 1 is that the thickness of the flexible transparent parylene film is 5.5 μm by adjusting the deposition parameters of the chemical vapor deposition method in step (1).

[0110] The rest of the preparation methods and parameters were the same as those in Example 1.

[0111] Example 5

[0112] The difference between this embodiment and embodiment 1 is that the line width of the metal network is 20 μm by adjusting the parameters of the laser etching method and the electroplating method in step (1).

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Example 6

[0115] The difference between this embodiment and embodiment 1 is that the line width of the metal network is 60 μm by adjusting the parameters of the laser etching method and the electroplating method in step (1).

[0116] The rest of the preparation methods and parameters were the same as those in Example 1.

[0117] Example 7

[0118] The difference between this embodiment and embodiment 1 is that the line spacing of the metal network is 0.1 mm by adjusting the parameters of the laser etching method and the electroplating method in step (1).

[0119] The rest of the preparation methods and parameters were the same as those in Example 1.

[0120] Example 8

[0121] The difference between this embodiment and embodiment 1 is that the line spacing of the metal network is 1 mm by adjusting the parameters of the laser etching method and the electroplating method in step (1).

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 9

[0124] The difference between this embodiment and embodiment 2 is that the spin coating parameters of the polydimethylsiloxane film in step (1) are adjusted so that the thickness of the polydimethylsiloxane film is 0.5 μm.

[0125] The rest of the preparation methods and parameters were the same as those in Example 2.

[0126] Example 10

[0127] The difference between this embodiment and embodiment 2 is that the spin coating parameters of the polydimethylsiloxane film in step (1) are adjusted so that the thickness of the polydimethylsiloxane film is 5 μm.

[0128] The rest of the preparation methods and parameters were the same as those in Example 2.

[0129] Comparative Example 1

[0130] The difference between this comparative example and Example 1 is that no metal grid is provided, that is, the double-sided conductive grid film is only composed of a single flexible transparent layer.

[0131] The rest of the preparation methods and parameters were the same as those in Example 1.

[0132] Comparative Example 2

[0133] The difference between this comparative example and Example 1 is that the double-sided conductive mesh film is replaced by an ITO layer.

[0134] The rest of the preparation methods and parameters were the same as those in Example 1.

[0135] Performance Testing

[0136] The photovoltaic performance of the stacked solar cells provided in the above embodiments and comparative examples was tested.

[0137] Test conditions: AM1.5, 1000W / m 2 , 25±2℃.

[0138] The test results are shown in Table 1.

[0139] Table 1

[0140]

[0141] analyze:

[0142] As can be seen from the above table, the present invention uses a double-sided conductive mesh film as an intermediate connecting layer and provides an optional port usage method. In the two-terminal stacked battery, the top battery is flexible, light and thin and has good coverage. It breaks through the time and space limitations of the traditional two-terminal stacked battery in the preparation process. Not only does it allow the top battery and the bottom battery to be prepared independently, but it also improves the battery efficiency and greatly saves the preparation cycle of the two-terminal stacked battery. The stacked solar cell has excellent photoelectric conversion efficiency.

[0143] It can be seen from Examples 1 and 3-4 that if the thickness of the flexible transparent parylene film is too small, it is not conducive to the effective transmission and uniform collection of current, resulting in an increase in series resistance, a decrease in fill factor, and a decrease in battery efficiency; if the thickness of the flexible transparent parylene film is too large, it is not conducive to light transmission, resulting in a decrease in short-circuit current density and a decrease in battery efficiency.

[0144] It can be seen from Example 1 and Examples 5-6 that if the line width of the metal network is too small, it is not conducive to the effective conduction of current, resulting in an increase in series resistance, a decrease in fill factor, and a decrease in battery efficiency; if the line width of the metal network is too large, it is not conducive to light transmission, resulting in a decrease in the amount of light entering the active layer, a decrease in short-circuit current density, and a decrease in battery efficiency.

[0145] It can be seen from Example 1 and Examples 7-8 that if the line spacing of the metal network is too small, it is not conducive to the transmission and absorption of light, resulting in a decrease in short-circuit current density and a decrease in battery efficiency; if the line spacing of the metal network is too large, it is not conducive to the efficient transmission of carriers, resulting in a decrease in open-circuit voltage and short-circuit current, and a decrease in battery efficiency.

[0146] It can be seen from Examples 2 and 9-10 that if the thickness of the polydimethylsiloxane film is too small, it will be unfavorable for insufficient current transmission, resulting in a decrease in the open circuit voltage of a single battery, and then a decrease in battery efficiency; if the thickness of the polydimethylsiloxane film is too large, it will be unfavorable for lightweight preparation and high light transmittance of the device, resulting in a decrease in overall efficiency.

[0147] It can be seen from Example 1 and Comparative Example 1 that if no metal grid is provided, that is, the double-sided conductive grid film is only composed of a single flexible transparent layer, the series structure device cannot be turned on.

[0148] It can be seen from Example 1 and Comparative Example 2 that if the double-sided conductive mesh film is replaced with an ITO layer, the series resistance increases, resulting in a decrease in the short-circuit current and efficiency.

[0149] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A tandem solar cell with a dual-mode port, characterized in that: The tandem solar cell is a two-terminal tandem solar cell or a four-terminal tandem solar cell; The stacked solar cell comprises a top cell, a bottom cell and a double-sided conductive mesh film located between the top cell and the bottom cell; The double-sided conductive mesh film comprises a metal mesh and a flexible transparent layer filled in the meshes of the metal mesh.

2. The tandem solar cell according to claim 1, characterized in that: The thickness of the double-sided conductive mesh film is 1-5 μm; Preferably, the line width of the metal grid is 30-50 μm; Preferably, the line spacing of the metal grid is 0.2-0.8 mm; Preferably, the metal grid is a rectangular grid.

3. The tandem solar cell according to claim 1, characterized in that: The material of the metal grid includes any one of nickel, copper or zinc or a combination of at least two thereof; Preferably, the flexible transparent layer comprises any one of a polyethylene terephthalate layer, a polycarbonate layer or a parylene layer, or a combination of at least two thereof; Preferably, in the double-sided conductive mesh film, the duty cycle of the metal mesh is 5-8%; Preferably, the thickness of the metal grid is equal to the thickness of the flexible transparent layer.

4. The tandem solar cell according to claim 1, characterized in that: The flexible transparent layer is a single-layer flexible transparent layer or a composite flexible transparent layer; Preferably, the composite flexible transparent layer comprises a bottom flexible transparent layer, an adhesive layer and a top flexible transparent layer which are stacked; Preferably, the thickness ratio of the bottom flexible transparent layer to the top flexible transparent layer is 1:(0.5-2); Preferably, the thickness of the bonding layer is 1-5 μm; Preferably, the material of the bonding layer includes any one of polydimethylsiloxane, polymethyl methacrylate or polyurethane, or a combination of at least two of them.

5. The tandem solar cell according to claim 1, characterized in that: The top cell comprises a perovskite solar cell; Preferably, the perovskite solar cell includes a transparent electrode layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and an electrode stacked in a direction away from the double-sided conductive grid film; Preferably, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties; Preferably, the bottom cell comprises any one of a silicon-based cell, a copper indium gallium selenide cell, a cadmium telluride cell or a perovskite solar cell, or a combination of at least two thereof.

6. A method for preparing a tandem solar cell with a dual-mode port according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: A top cell is prepared on one side surface of a double-sided conductive mesh film and then stacked on a bottom cell so that the other side surface of the double-sided conductive mesh film fits the bottom cell to obtain the stacked solar cell with a dual-mode port.

7. The preparation method according to claim 6, characterized in that: The method for preparing the double-sided conductive mesh film comprises the following steps: Depositing a flexible transparent film on a rigid substrate, and then patterning the flexible transparent film to form a blank grid, wherein the blank grid exposes the rigid substrate; The blank grids are filled with metal material to form metal grids, and then the rigid substrate is peeled off to obtain the double-sided conductive grid film.

8. The preparation method according to claim 7, characterized in that: The rigid substrate includes any one of a conductive silicon wafer, ITO glass or FTO glass; Preferably, the deposition method of the flexible transparent film includes any one of a solution processing method, a physical vapor deposition method or a chemical vapor deposition method; Preferably, the patterning process includes any one of laser etching, photolithography, screen printing or thermal evaporation; Preferably, the filling method of the metal material comprises an electroplating method, in which the current is 30-50 mA and the electroplating time is 10-20 min.

9. The preparation method according to claim 7, characterized in that: The flexible transparent film is a single-layer flexible transparent film or a composite flexible transparent film; Preferably, the method for preparing the composite flexible transparent film comprises: Depositing a bottom flexible transparent film, a bonding layer and a top flexible transparent film in sequence on one side surface of the rigid substrate; The preparation method of the bonding layer includes a solution method.

10. Application of the tandem solar cell with dual-mode ports according to any one of claims 1 to 5 in the photovoltaic field.